Pterostilbene restores mitochondrial retrograde signaling to activate protective stress responses in Parkinson’s disease - Zeng, Fanshuai; Li, Wei; Yang, Liyue; Yao, Lu; Wang, Xinna (Frontiers in Aging Neuroscience, 2025)
Parkinson’s disease (PD) is the selective demise of dopaminergic neurons in the substantia nigra. Conventional neuroprotective strategies based on exogenous antioxidants have shown minimal clinical efficacy. Emerging evidence suggests that neuronal loss in PD may stem not only from direct mitochondrial damage but, more critically, from the failure of an intrinsic “early-warning system”—the mitochondrial retrograde signaling (MRS) pathway—impairing the nucleus’s ability to launch timely protective responses. This review repositions pterostilbene, a bioavailable dietary polyphenol, from a simple antioxidant to a “signal fidelity enhancer” that supports mitochondria-to-nucleus communication. By stabilizing mitochondrial function and modulating stress-sensing pathways, pterostilbene may restore MRS integrity and promote activation of endogenous defense mechanisms such as the mitochondrial unfolded protein response (UPRmt). The article advocates a paradigm shift in nutritional neuroprotection: from passive supplementation toward reinforcing the neuron’s intrinsic capacity for self-maintenance and resilience.